The Comic Art of Jane Austen: A New Approach Vs. The Plot of Pride and Prejudice - Priydarshi, Dr Ashok Kumar (Journal of Advanced Research in English & Education, 2025)
Jane Austenâ€™s â€œPride and Prejudiceâ€ is a masterfully constructed novel, where plot and character are intricately interwoven. Traditionally, the plot has been analyzed through the lens of romantic entanglements and social expectations. However, examining the narrative through the prism of Austenâ€™s comic art reveals a deeper understanding of her storytelling prowess. This article argues that Austenâ€™s use of wit, irony, and satire is not merely decorative but fundamental to the plotâ€™s progression. By dissecting key plot points, we will demonstrate how her comic techniques drive the narrative, expose character flaws, and ultimately resolve the central conflicts. Austenâ€™s comic art serves to highlight the absurdity of social conventions, the folly of hasty judgments, and the transformative power of self-awareness. Each twist and turn of the plot is infused with comedic elements that both entertain and enlighten, providing a critical commentary on the society she depicts. We will explore how Austen uses comic devices to create suspense, develop character arcs, and ultimately deliver a satisfying resolution. This approach offers a fresh perspective on the novel, revealing how Austenâ€™s comedic genius is integral to the plotâ€™s structure and thematic resonance, enriching our appreciation of her enduring literary achievement.